Guidance for Processing Fresh-cut Produce in Retail Operations - Keith R. Schneider; Victor Garrido; W. Steve Otwell; Ray Mobley (EDIS)
The International Fresh-cut Produce Association (IFPA) defines fresh-cut produce as "any fresh-cut fruit or vegetable or any combination thereof that has been physically altered but remains in the fresh state. These products are items such as bagged salads, baby cut carrots and broccoli florets." This definition covers a wide range of products which require vastly different handling practices. This definition is broadened to include the repacking of fresh-cut herbs and their use on packaged fresh-cut products manufactured in the retail setting and/or held for sale. This guidance will give general recommendations for fresh-cut produce, but is not intended to be applicable for all instances. This document is FSHN05-05, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. Published: February 2005.